Penguatan Peran Suami pada Masa Kehamilan Istri di Posyandu Krisan Cianjur - Ratnayani, Ratnayani; Avicena, Rasyid; Halimatushadyah, Ernie; Rahmadianti, Julia Dwi; Zulham, Edvan Duta; Rizkiyawati, Rizkiyawati; Hidyatussabilah, Hidyatussabilah (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2024)
Sukanagalih is one of the villages located in Pacet District, Cianjur Regency, West Java and is one of the villages fostered by Binawan University. The problem of pregnant women with Chronic Energy Deficiency (KEK) still occurs in Cianjur Regency. The problem of KEK needs to be handled and given attention by related parties. The role of the family, especially the husband, can affect the health of pregnant women. Based on this, community service was carried out with the main target being pregnant women by involving cadres from the Krisan Posyandu. In this activity, the husbands of pregnant women were involved to be given education related to pregnancy and how to prepare food during pregnancy. By involving husbands, it is hoped that the mother will have a healthy pregnancy and will give birth to a healthy baby. This community service aims to provide education and involve husbands regarding the scope of pregnancy and the provision of nutritious food for pregnant women using food and herbal local. The stages of community service activities carried out are continued potential surveys, implementation of educational activities and cooking competitions, as well as evaluation and reporting. Based on the survey results, to expand the benefits of the activity, education participants are not only limited to pregnant women and their husbands but also other residents who live in the area. Providing education to residents has increased the knowledge of the participants. Before the education was carried out, the average level of knowledge was 47.70 and after being given education it increased to 85.31. In addition, the cooking competition activities that were carried out have made residents more creative in utilizing local food ingredients and herbs into various types of food and drinks. Seeing the results obtained, residents of Sukanagalih Village have the potential to be given further assistance.